Unexpected subdiaphragmatic benign cyst - Melania Macarie; Alexandra Pais; Calin Molnar; Razvan Valerian Opaschi; Minodora Maria Șchiopea Zolog; Simona Maria Bățagă; Ioan Macarie (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Macarie M, Pais A, Molnar C, et al. Unexpected subdiaphragmatic benign cyst. Turk J Gastroenterol 2020; 31(11): 829-30.